2019
DOI: 10.3390/cryst9060316
|View full text |Cite
|
Sign up to set email alerts
|

Structural Insights into the Two-Step Spin-Crossover Compound Fe(3,4-dimethyl-pyridine)2[Ag(CN)2]2

Abstract: The crystal structure of the polymeric spin crossover compound Fe(3,4-dimethyl-pyridine)2[Ag(CN)2]2 has been solved and its temperature dependence followed by means of single-crystal and powder X-ray diffraction. This compound presents a two-step spin transition with relatively abrupt steps centred at ca. 170 K and 145 K and a plateau at around 155 K. The origin of the two-step transition is discussed in light of these structural studies. The observations are compatible with a mostly disordered state between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 29 publications
(39 reference statements)
0
5
0
Order By: Relevance
“…The transition temperatures are 175 K ( T c1 ) and 125 K ( T c2 ), with a narrow pseudoplateau appearing between 145 and 149 K. In the subsequent heating mode, these parameters are completely retained, and the transition curve reproduces the curve in the cooling regime. It was found that AgPhpz is characterized by transition temperatures similar to those of Ag-containing SCO complexes based on pyridine-type ligands. ,,, …”
Section: Resultsmentioning
confidence: 94%
See 3 more Smart Citations
“…The transition temperatures are 175 K ( T c1 ) and 125 K ( T c2 ), with a narrow pseudoplateau appearing between 145 and 149 K. In the subsequent heating mode, these parameters are completely retained, and the transition curve reproduces the curve in the cooling regime. It was found that AgPhpz is characterized by transition temperatures similar to those of Ag-containing SCO complexes based on pyridine-type ligands. ,,, …”
Section: Resultsmentioning
confidence: 94%
“…Complex AgPhpz undergoes a gradual two-step transition over a temperature range of ∼100 K (Figure 4a) like for similar Ag-containing SCO systems. 32,36,44 The χ M T values are 3.53 cm 3 K mol −1 at 273 K, 1.86 cm 3 K mol −1 at 147 K, and 0.23 cm 3 K mol −1 at 50 K, which allow one to roughly estimate the completeness of the transition at 0%, 47%, and 94%, respectively. This corroborates with the complete stepped transformation of a Fe(II) ion from the HS state (S = 2, paramagnetic) to the LS state (S = 0, diamagnetic).…”
Section: ■ Experimental Sectionmentioning
confidence: 99%
See 2 more Smart Citations
“…The optical microscopy technique to investigate the thermal and the spatio-temporal properties of the Hofmann-related SCO single crystal [Fe(2-pytrz) 2 {Pt(CN) 4 }]_3H 2 O was described to show a first-order SCO behavior from a full high-spin (HS) state at high temperatures to intermediate, high-spin low-spin (HS-LS) states [14]. The precise crystallographic investigation on the polymeric SCO Hofmann-like compound Fe(3,4-dimethyl-pyridine) 2 [Ag(CN) 2 ] 2 was reported, and its temperature dependence was followed by the means of a single-crystal and powder X-ray diffraction [15]. These very important article reported in the special issue demonstrate a soft X-ray-induced excited spin state trapping (SOXEISST) effect in Hofmann-like SCO coordination polymers of Fe II (4-methylpyrimidine) 2 [Au(CN) 2 ] 2 and Fe II (pyridine) 2 [Ni(CN) 4 ] [16].…”
mentioning
confidence: 99%